Accent Speaks Louder than Ability: Elucidating the Effect of Nonnative Accent on Trust. Issue 3 (June 2023) - Geiger, Mingang K.; Langlinais, Luke A.; Geiger, Mark
Nonnative accent often leads to prejudicial judgments. In this paper, we examine the effect of a job candidate's Mandarin Chinese accent on a hiring manager's perceptions of trust and the three dimensions of trustworthiness. The results of an online experiment with 179 working adults suggest that speaking with a nonnative accent (vs. no accent) adversely affects hiring decision-makers' perceptions of trust and the ability dimension of trustworthiness, but not the benevolence and integrity dimensions. We also examined the effects of perspective taking (vs. no perspective taking) on trust and trustworthiness to test its beneficial role in interpersonal evaluations. The findings suggest that perspective taking may significantly mitigate the effect of language-based stigma on people's judgments, providing evidence-based insights for organizational leaders and HR professionals.